Fake aggression, true excitement: the daily "back-and-forth" ceremony at Wagah border - Usman, Muhammad; Harder, Hans (Ruperto Carola, 2025)
A site of both peaceful co-existence and violent bloodshed, the Wagah section of the border between India and Pakistan has emerged as an arena in which cultural, political and religious ideas about nationhood play out to this day. Since the Partition of India in 1947, the Wagah border crossing has seen a constant back and forth of people, goods and ideas. Today, it is the site of an extraordinary spectacle: the so-called Wagah Border Ceremony. During this highly ritualized display, paramilitary soldiers on both sides of the border march towards and away from each other, capturing the complex relationship between India and Pakistan in a delicate choreography. Research conducted at Heidelberg University focuses on how the enmity between the two nation states is staged during the ceremony and in what way it might quite paradoxically also conjure ideas of friendly competition.
Veröffentlicht: 2025-02-24
Gesehen am 26.02.2025